The Posterior Use of BMP-2 in Cervical Deformity Surgery Does Not Result in Increased Early Complications: A Prospective Multicenter Study - Iyer, Sravisht (Global Spine J, 2018)
STUDY DESIGN: Prospective cohort study. OBJECTIVES: To describe the rate of short-term complications following the posterior use of recombinant human bone morphogenetic protein–2 (rhBMP-2) in cervical deformity (CD) surgery. METHODS: CD patients from 2013 to 2015 were enrolled in a prospective, multicenter database. Patients were divided into those receiving rhBMP-2 (BMP) and no rhBMP-2 (NOBMP). The relationship between BMP use, demographic variables surgical variables, radiographic parameters and complications was evaluated. RESULTS: A total of 100 patients (47 BMP, 53 NOBMP) were included. Follow-up time averaged 7.6 months (range 3-12 months). An average of 13.6mg of BMP was used per person with 1.49 mg per level. Compared with the NOBMP group, patients in the BMP group were older (P = .03). BMP was more commonly used in patients that and had longer prior fusions (6.0 vs 2.5, P < .01). There were no differences between groups with regards to a history of surgery, Charlson Comorbidity Index, estimated blood loss, operation time, fusion levels, and surgical approach. The maintenance of radiographic parameters at 6-month follow-up was similar. There were no differences in terms of total complication incidence, total complications per person, major complications per person or any specific complication. Linear regression and Pearson correlation analysis did not reveal any strong r(2) values (r(2) = 0.09, 0.08, 0.06) between the use of BMP and complications (major or operative). CONCLUSIONS: BMP use was not directly associated with an increased incidence of early complications in this prospective cohort of operative adult CD patients. Its use was associated with increased number of levels instrumented and fused.